Violence: A problem of mental health in Peru: La violencia: ¿Un problema de salud mental en el Perú? - Fernandez Rojas, Laurie Susana (2020)
WHO defines mental health as a condition in which a person is aware of his or her abilities to face the problems of everyday life, performs productively in his or her workplace, and contributes to his or her community. During 2017, according to the Ministry of Health in Peru, 52,611 people were treated on an outpatient basis for mental health among victims of family violence and patients with different mental disorders. The number of victims of family violence was 18,387.